Creating a Psychologically Safe Environment for Interaction between the Teacher and the Parents of Pupils as One of the Conditions for the Formation of a Single Educational Space for the Development of a Preschooler - Kazarova, E.G. (Bulletin of Practical Psychology of Education, 2020)
The article analyzes the degree of public understanding of the role of parents and teachers in the education and upbringing of a preschooler, substantiates the relevance of the problem associated with understanding of this role. The article also considers the structure of psychological safety of interaction of a kindergarten teacher with parents of pupils. The interaction among the participants of the educational process is considered as one of the conditions for the formation of unified educational space for the development of preschool children both in a family and in a kindergarten. The article provides practical recommendations upon the creation of psycho-pedagogical conditions for safe interaction among the participants of pre-school educational process. Specific possibilities of participation of parents in the activities of the kindergarten are considered. The question of self-regulation of the emotional state of teachers, prevention of their emotional burnout and conflict is raised. The proposed recommendations can be used in the professional activities of teachers and teacher-psychologist of a preschool educational institution. В статье анализируется степень понимания обществом роли родителей и педагогов в образовании и воспитании дошкольника, обосновывается актуальность проблемы, связанной с пониманием этой роли. Также рассматривается структура психологической безопасности — как составляющей части всего процесса взаимодействия педагога детского сада с родителями воспитанников. Взаимодействие участников образовательного процесса рассматривается как одно из условий формирования единого образовательного пространства развития дошкольника в семье и детском саду. В статье даются практические рекомендации по созданию психолого-педагогических условий для безопасного взаимодействия участников образовательного процесса в дошкольном образовательном учреждении. Рассматриваются конкретные возможности участия родителей в деятельности детского сада. Затрагивается вопрос саморегуляции эмоционального состояния педагогов, профилактики их эмоционального выгорания и конфликтности. Предложенные рекомендации могут быть использованы в профессиональной деятельности воспитателей и педагога-психолога дошкольного образовательного учреждения.